THE INFLUENCE OF GENDER DIFFERENCES ON REPORTING AND HANDLING VIOLATIONS OF PROFESSIONAL ETHICS AMONG LAWYERS - Tahara, Aisyah; Nurwandri, Andri; Ni’mah , Siti; Harahap, Walijah Fitriyah (PT. Jurnal Center Indonesia Publisher, 2025)
This research aims to analyze the influence of gender differences on reporting and handling professional ethics violations among lawyers. Gender differences are believed to influence how individuals interact with the rules and norms in the legal profession, including when it comes to reporting ethical violations. This research examines how male and female lawyers respond to ethical violations that occur in their environment as well as the factors that influence their decisions to report or address these violations. The research results show significant differences in the way male and female lawyers handle violations of professional ethics. Factors such as perception of authority, influence of organizational culture, and professional experience also influence their behavior. This research also found that female lawyers tend to be more sensitive to issues of ethical violations and report cases that occur more often than male lawyers. These findings provide new insights regarding gender dynamics in the legal profession and the importance of creating a more inclusive environment in dealing with violations of professional ethics.